2013
DOI: 10.3390/brainsci3010101
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Motor Function by Exercising the Brain

Abstract: Exercise represents a behavioral intervention that enhances brain health and motor function. The increase in cerebral blood volume in response to physical activity may be responsible for improving brain function. Among the various neuroimaging techniques used to monitor brain hemodynamic response during exercise, functional near-infrared spectroscopy could facilitate the measurement of task-related cortical responses noninvasively and is relatively robust with regard to the subjects’ motion. Although the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 106 publications
(139 reference statements)
3
38
1
1
Order By: Relevance
“…(20) They attributed task-induced vasodilatation to an increased demand for cerebral metabolism in response to neuronal activity, and found that during physical activities, CBF increases to supply adequate oxygen into the brain, and the CBF regulation seems to be crucial for the maintenance of cardiovascular homeostasis. (20,30) IAHF potency for vessel recanalization was not observed in this study. Substantial experimental data andrecent clinical evidences suggested that tissue reperfusion is a better predictor for after-thrombolysis outcome compare to recanalization.…”
Section: Pre-testcontrasting
confidence: 66%
“…(20) They attributed task-induced vasodilatation to an increased demand for cerebral metabolism in response to neuronal activity, and found that during physical activities, CBF increases to supply adequate oxygen into the brain, and the CBF regulation seems to be crucial for the maintenance of cardiovascular homeostasis. (20,30) IAHF potency for vessel recanalization was not observed in this study. Substantial experimental data andrecent clinical evidences suggested that tissue reperfusion is a better predictor for after-thrombolysis outcome compare to recanalization.…”
Section: Pre-testcontrasting
confidence: 66%
“…BDNF is a key protein in the regulation for the sustainability of growth, for the life of neurons and important activity of synaptic transmission. On physical exercises, BDNF can stimulate neurogenesis in the form of the formation of new neurons [22,24,46]. The study result ( Table- Not many explanations of the relation of CRP and AD [33].…”
Section: Discussionmentioning
confidence: 85%
“…So far, study on the improvement of exercise-induced brain plasticity has not been widely reported (Perrey, 2013). This study has not been performed in Indonesia.…”
Section: Introductionmentioning
confidence: 97%
“…1 Although propensity analysis was conducted to account for the potential confounding patient characteristics identified during the initial ED present-tion, the observational nature of the study means that additional unmeasured confounders might have influenced the result. Furthermore, it is only possible to draw a conclusion of an association between earlier resumption of physical activity and reduced incidence of PPCS, rather than a direct causation.…”
Section: Follow-up Period 28 Daysmentioning
confidence: 99%